Luminescent properties and stability of Eu²⁺ ions in SrBPO₅ and SrAl₂B₂O₇ - Pir, P.V.; Dotsenko, V.P.; Efryushina, N.P; Klimenko, Z.D. (Functional Materials, 2007)
Using the luminescence spectroscopy, the stability of Eu²⁺ ions in SrBPO₅ has been shown to exceed significantly that in SrAl₂B₂O₇. The luminescence spectrum of Eu²⁺ in SrBPO₅ and SrAl₂B₂O₇ consists of a broad band with a maximum at 390 and 490 nm, respectively. In contrast to SrBPO₅, the stabilization of Eu²⁺ ions in SrAl₂B₂O₇ requires an annealing in reducing medium. It is supposed that this is caused by the difference in the effectiveness of the excess charge compensating processes for Eu³⁺ which can be quantified by the formal volume per oxygen atom (V₀) in the compound structure.